WRONG WRITING IN THE QUR'AN: PALEOGRAPHIC STUDIES AS A CRITIQUE OF THE LUXENBURG THESIS - Zakiyah, Ermita; Riyadi, Abdul Kadir; Yani, Achmad (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
The purpose of this study is to answer the thesis presented by Luxenberg. He states that the Qur'an is not Arabic. He assumes that the Qur'an has errors in its writing. The letters develop and are not by the beginning of its revelation. The tradition that changed from memorized tradition to written tradition also has a high possibility of being wrong, according to Luxenberg. This research uses the theory of interpretation criticism because what Luxenberg states as an orientalist is very different from the Islamic scientific tradition. The data analysis in this research uses literature data. Luxenberg's statement was analyzed and criticized using Islamic science and Palaeography. By using the theory and data analysis, it is established that Luxenberg's thesis is erroneous because the wrong writing of the Qur'an will never happen, either with the paleographic study presented by Luxenberg or with the study of the History of the Qur'an from the time of the Prophet until codification.